Antibacterial activity, physical and chemical properties of sweet corn milk kefir with variation of starter concentration and fermentation time - Mulyaningsih Sri; Apriliyanti Nurdiana (BIO Web of Conferences)
Sweet corn is a potential raw material for kefir production due to its high carbohydrate content. The purpose of this study was to determine the effect of starter concentration and fermentation time on the properties of sweet corn milk kefir and to find the optimal starter concentration and fermentation time. The kefir was prepared with starter concentrations of 2%, 4%, 6%, with fermentation times ranging from 8, 16, 32, 40, 48, 56, 64, and 72 hours. Organoleptic tests, pH, acid content, and antibacterial activity were studied. The results obtained were analyzed statistically. The results showed that starter concentration and fermentation time significantly affected organoleptic properties, pH, lactic acid content, and antibacterial activity (P<0.05). The longer the fermentation time, the lower the pH value, the higher the acid content, and the higher the antibacterial activity. The fermentation time of 64 hours and 4% starter concentration showed a pH value of 3.46 with the highest acid content of 2.107% and an inhibition zone diameter of 11.02 mm. Starter concentration and fermentation time of kefir significantly influenced organoleptic properties, pH, acid content, and antibacterial activity against V. cholerae. The optimal kefir was obtained at 4% starter concentration and 64 hours of fermentation time.